Fragmented QRS on electrocardiography as a predictor for diastolic cardiac dysfunction in type 2 diabetes. Issue 6 (16th February 2022) - Yagi, Kunimasa; Imamura, Teruhiko; Tada, Hayato; Liu, Jianhui; Miyamoto, Yukiko; Ohbatake, Azusa; Ito, Naoko; Shikata, Masataka; Enkaku, Asako; Takikawa, Akiko; Honoki, Hisae; Fujisaka, Shiho; et al.
Abstract: Aims/Introduction: Diastolic cardiac dysfunction in type 2 diabetes (DD2D) is a critical risk of heart failure with preserved ejection fraction. However, there is no established biomarker to detect DD2D. We aimed to investigate the predictive impact of fragmented QRS (fQRS) on electrocardiography on the existence of DD2D. Materials and Methods: We included in‐hospital patients with type 2 diabetes without heart failure symptoms who were admitted to our institution for glycemic management between November 2017 and April 2021. An fQRS was defined as an additional R′ wave or notching/splitting of the S wave in two contiguous electrocardiography leads. DD2D was diagnosed according to the latest guidelines of the American Society of Echocardiography. Results: Of 320 participants, 122 patients (38.1%) had fQRS. DD2D was diagnosed in 82 (25.6%). An fQRS was significantly associated with the existence of DD2D (odds ratio 4.37, 95% confidence interval 2.33–8.20; p  < 0.0001) adjusted for seven potential confounders. The correlation between DD2D and diabetic microvascular disease was significant only among those with fQRS. Classification and regression tree analysis showed that fQRS was the most relevant optimum split for DD2D. Conclusions: An fQRS might be a simple and promising predictor of the existence of DD2D. The findings should be validated in a larger‐scale cohort. Abstract : Fragmented QRS was significantly associated with diastolic cardiac dysfunction in type 2 diabetes independent of other risk factors. Diastolic cardiac dysfunction in type 2 diabetes correlated with the number of diabetic microvascular diseases only significantly in the individuals with fragmented QRS.